Pembagian Hak Harta Waris Bagi Bayi dalam Kandungan (Perbandingan Mazhab Syafi’i dan Mazhab Hambali) - Mustofa, Heva Derika; Imron, M Zuhdi; Gibtiah, Gibtiah (Muqaranah, 2023)
A baby who is still in the womb is an heir who has the right to inherit inheritance, so in implementing the division of inheritance, there are problems in itself because there is no certainty regarding the baby being born whether the baby was born alive or dead, whether the gender is male or female, and born alone or twins. Therefore, this article will examine the determination of inheritance rights for unborn babies from the perspective of the Shafi'i school of thought and the Hanbali school of thought. The aim of this research is to determine the position of inheritance rights for unborn babies from the perspective of the Shafi'i school of thought and the Hambali school of thought. The method used in this research is library research, namely searching for data through existing literature and then drawing conclusions to answer the problems that have been formulated. The results of this research conclude that determining the inheritance rights of unborn babies according to the Syafi'i school of thought should be postponed until the baby is born. According to the Hambali school of thought, inheritance can be given to heirs without having to wait for the birth of the baby. by setting aside a portion of the inheritance of the baby in the womb (deferred) for two boys or two girls with presumptive twins